Relationship Engagement in Mergers and Acquisitions through Collegial Leadership - Jedin, Mohd Haniff; Saad, Norsafinas Md (International Journal of Economics and Financial Issues, 2016)
Research on the relationship engagement in Mergers and Acquisitions (M&As) is still unclear although this phenomenon has been explored in the global multi-business environment. Existing researches did not clearly demonstrate the importance of the relationship among M&A players in the amalgamation processes between an acquirer and the acquired firm. Thus, this paper attempts to highlight the influence of collegial leadership in initiating relationship engagement in the post M&A integration. Result shows that collegial leadership significantly influence the relationship engagement in M&A. Keyword: Mergers and Acquisitions; Relationship engagement; Collegiality JEL Classification: G34